Maintenance of male sterile germplasm in Brassica rapa by in vitro propagation - GUO, Y.-D.; NIEMELÄ, T.; TULISALO, U. (Agricultural and Food Science, 2000)
An efficient tissue culture system for plant regeneration, from mature cut branches, was established to maintain male sterile material in Brassica rapa L. The new-growth immature pods from the cut branches were used as explantsresults in callus initiation (37 calli from 25 explants) and shoot formation (17 shoots from 75 explants) than flower buds and branch stems. Auxin [2,4-dichlorophenoxyacetic acid (2,4-D), 2 to 5 mg l-1] and cytokinin [6-benzylaminopurine (BA), 2 to 4 mg l-1] were essential in callus and shoot formation, respectively. Callus initiation and shoot regeneration capacities were genotype dependent. The regenerated plants were male sterile and were used in breeding programs.;